Minecrafter architect : the builder's idea book - Miller, Megan, 1963- (Unofficial minecrafter's guide., 2019)
Offers players dozens of examples of window treatments, entranceways, roofs, walls, paths, roads, and bridges that they can copy into their own game play or become inspiration for new Minecraft builds.